Mineral Content of "Aren Sap" and of "Granulated Aren Sugar") - Suryati, Atih; -, Herman; Yunus, M (Warta Industri Hasil Pertanian, 1987)
Mineral content af aren sap and of garnulated aren sugar had been analyzed. Seventeen samples of juice were collected from trees of Arenga pinnata MERR in Sukabumi and Cianjur; while 48 samples of granulated aren sugar were collected from home industries in the same area. Both sugar and sap have a mineral content between 1 to 1.8 percent dry basis (1.5 more or less than 0.22). The major mineral component of the sap was pottasium (K), followed by phosphor (P), magnesium (Mg), sodium (Na), calcium (Ca), ferrum (Fe) and cuprum (Cu), with the content of 8296, 776, 733,619, 53, 10 and 6 milligram/kg dry basis respectively.